Population growth of ROTIFERS (Brachionus rotundiformis) FED with Vitamin B12-enhanced NANNOCHLOROPSIS OCULATA. - Bulaclac, Dorothy Grace P. (UPHSI, 2009)
This study aimed to know what amount of Vitamin B12 in Nannochloropsis oculata will result into a more significant increase in rotifer density. There were four treatments with three replicates each. Three of these treatments were the N. oculata enhanced with different concentrations of Vitamin B12, and the other treatment was the control, containing pure N. oculata. Data gathering which included the feeding and counting of rotifers were done every 24 hours, within 10 days. Population growth of rotifers, Branchionus rotundiformis, was determined using the Sedgewick-Rafter counting chamber. One-way ANOVA followed by the Duncan's Multiple Range Test (DMRT) were used in comparing set-ups. Although set up three with Nannochloropsis ocula + 583 Vitamin B12 yielded teh higest density for rotifers, the results showed that there was no significant difference on the population growth of the rotifers among the four treatments.